A study of the influence of iron, phosphate, and silicate in Si uptake by two Synechococcus strains - Godrant, Aurélie; Leynaert, Aude; Moriceau, Brivaela (Frontiers in Marine Science, 2024)
We investigated the influence of iron (Fe), phosphate (PO4), and silicic acid [Si(OH)4] concentrations on Si uptake rate by two strains of Synechococcus. Growth rates, cellular biogenic silica (bSi), and silicon uptake rates were measured and compared. Both strains showed significant Si cellular contents varying from 0.04 47 fmol cell−1 to a maximum of 47 fmol cell−1, confirming that the presence of Si in Synechococcus is a common feature of the genus but with strain specificity. Maximum Si cell contents were measured when Fe and P co-limited RCC 2380 growth (47 fmol Si cell−1) and under -Fe-Si limitations (6.6 fmol Si cell−1) for the second strain RCC 1084. Unambiguously, all conditions involving P limitations induced an increase in the Si uptake by the two Synechococcus. Moreover, RCC 1084 showed a relationship between Si cellular quota and growth rate. However, both strains also showed a clear impact of Fe concentrations on their Si uptake: Si quotas increased 1) under Fe limitation even without P co-limitation and 2) under simple Fe limitation for RCC 1084 and with Si co-limitations for RCC 2380. Both strains exhibited a behavior that has never been seen before with changing Si(OH)4: concentrations of 150 µM of Si(OH)4 negatively impacted RCC 2380 growth over 10 generations. Conversely, RCC 1084 was limited when Si(OH)4 concentrations dropped to 20 µmol L−1. Maximum Synechococcus Si uptake rates normalized to the organisms’ size (7.46 fmol µm−3 day−1) are comparable to those measured for diatoms and rhizarians. From our data, and using all the data available on Synechococcus Si content and Si uptake rates, their average concentrations for each Longhurst province, and existing descriptions of the dominant nutrient limitations and Synechococcus strain specificity, we estimated at the global scale that the annual bSi stock contained in Synechococcus is 0.87 ± 0.61 Tmol Si, i.e., around a quarter of the bSi stock due to diatoms. We also estimated that the global Si production due to Synechococcus could average 38 ± 27 Tmol Si year−1, which is roughly 17% of the total global annual Si production.